GERAKAN BUPOLO MAGHRIB MENGAJI SEBAGAI MEDIA PRURALISME - Wabula, Abdul Latif; Umanailo, M. Chairul Bahrun; Kurniawan, Rudi; Rusdi, M.; Nuthihar, Rahmat (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
Bupolo Maghrib Mengaji Movement is a form of social community movement initiated by the Buru’s Government with the Ministry of Religion of Buru Regency as an effort to spend maghrib time and to avoid the Buru community from the negative impact of technological developments and make the movement as a media to achieve pluralism. This research is a qualitative study which aims to describe the implementation of the Bupolo Maghrib Mengaji Movement in Namlea District, Buru Regency. The research location was focused on Namlea District with consideration of the density and heterogeneity of the community. The number of informants who will be interviewed was 25 people who were taken purposively. The technique of analysis used by Miles and Huberman in the form of data reduction, data presentation, and conclusion drawing. The results showed that the Bupolo Maghrib Mengaji Movement received a positive response from the community where the initiation carried out by the community was able to become an instrument of achieving harmonization of community life to maintain and to remind each other in spending Maghrib time. Also, the sectoral mapping of community activities in the Bupolo Maghrib Mengaji Movement raises two components namely moral and ethics which functioned to foster and maintain pluralism in Namlea District. Pluralism is an important basis for living tolerantly in a society that is different from tribes, groups, religions and customs.